Stability, dynamics, and tolerance to undersaturation of surface nanobubbles - Tan, Beng Hau (2019)
The theoretical understanding of surface nanobubbles—nanoscale gaseous domains on immersed substrates—revolves around two contrasting perspectives. One perspective, which considers gas transport in the nanobubbles’ vicinity, explains numerous stability-related properties but systematically underestimates the dynamical response timescale by orders of magnitude. The other perspective, which considers gas transport as the bulk liquid equilibrates with the external environment, recovers the experimentally observed dynamical timescale but incorrectly predicts that nanobubbles progressively shrink until dissolution. We propose a model that couples both perspectives, which is capable of explaining the stability, dynamics, and unexpected tolerance of surface nanobubbles to undersaturated environments.